Spinal fMRI of Interoceptive Attention/Awareness in Experts and Novices - Keyvan Kashkouli Nejad; Motoaki Sugiura; Benjamin Thyreau; Takayuki Nozawa; Yuka Kotozaki; Yoshihito Furusawa; Kozo Nishino; Toshohiro Nukiwa; Ryuta Kawashima (Neural Plasticity)
Many disciplines/traditions that promote interoceptive (inner sensation of body parts) attention/awareness (IAA) train practitioners to both attend to and be aware of interoceptive sensory experiences in body parts. The effect of such practices has been investigated in previous imaging studies but limited to cerebral neural activity. Here, for the first time, we studied the impact of these practices on the spinal neural activity of experts and novices. We also attempted to clarify the effect of constant and deep breathing, a paradigm utilized in concentration practices to avoid mind wandering, on IAA-related spinal neural activity. Subjects performed IAA tasks with and without a deep and constant breathing pattern in two sessions. Results showed that neural activity in the spinal segment innervating the attended-to body area increased in experts (P=0.04) when they performed IAA and that this increase was significantly larger for experts versus novices in each of the sessions (P=0.024). The significant effects of IAA and expertise on spinal neural activity are consistent with and elaborate on previous reports showing similar effects on cerebral neural activity. As the spinal cord directly innervates body parts, the results might indicate that IAA has an instantaneous (possibly beneficial) effect on the physical body after extended training.